Decreased P‐glycoprotein is associated with the inhibitory effects of static magnetic fields and cisplatin on K562 cells. Issue 6 (6th August 2014) - Zhang, Kun; Chen, Wenfang; Bu, Ting; Qi, Hao; Sun, Runguang; He, Xiao
<x xml:space="preserve">Abstract</x> In this study, we explored the mechanism of the killing effects of a moderate‐intensity static magnetic field (SMF) and cisplatin (DDP) on K562 cells. We analyzed the metabolic activity of cells, the extracellular DDP content, and P‐glycoprotein (P‐gp) expression after K562 cells were exposed continuously to a uniform 8.8 mT SMF for 8 h, with or without DDP. We found that SMF combined with DDP (10 µg/ml) significantly inhibited the metabolic activity of K562 cells (P < 0.05), while neither DDP nor SMF alone affected the metabolic activity of these cells. In the SMF + DDP group, extracellular DDP content was significantly reduced (P < 0.05). DDP also induced the expression of P‐gp (P < 0.05). By contrast, in the SMF + DDP group, P‐gp expression decreased compared with the DDP group (P < 0.05). Taken together, our results showed that 8.8 mT SMF enhanced the killing potency of DDP on K562 cells by decreasing the expression of P‐gp. Bioelectromagnetics. 35:437–443, 2014. © 2014 Wiley Periodicals, Inc.